The Role of Sales Promotion, Strategic Location, and Brand Awareness in Customer Loyalty through Repurchase Intention: An Empirical Field Study - Haryudi Anas; Agus Dharmanto (Dinasti Review, 2026)
This study examines the role of sales promotion, strategic location, and brand awareness in strengthening customer loyalty through repurchase intention. The research was designed as a quantitative field survey involving 120 consumer respondents. Data were collected using a structured questionnaire measured with a five-point Likert scale and processed in SPSS-style statistical reporting and SmartPLS-style partial least squares structural equation modelling (PLS-SEM). The SPSS regression results indicate that sales promotion, strategic location, and brand awareness significantly predict repurchase intention (R² = 0.456), while customer loyalty is significantly explained by sales promotion, strategic location, brand awareness, and repurchase intention (R² = 0.497). The SmartPLS measurement model shows that all constructs meet reliability and convergent validity criteria, with Cronbach's alpha values ranging from 0.801 to 0.869, composite reliability values above 0.870, and AVE values above 0.626. The structural model confirms that strategic location is the strongest antecedent of repurchase intention, while repurchase intention also has a meaningful effect on customer loyalty. Mediation testing indicates that repurchase intention transmits the effects of sales promotion, strategic location, and brand awareness on loyalty, although the direct path from brand awareness to loyalty is comparatively weaker. These findings imply that customer loyalty is not formed only through transactional incentives or brand recognition, but also through repeated purchase motivation supported by accessible store location and consistent brand salience.